FLAC3D Simulation of Caving Mechanism and Strata Fracture Response in Underground Mining - Mahdi Saadat; Mattin Khishvand; Andrew Seccombe (Mining)
This paper presents an innovative numerical approach to simulating the progressive caving of rock mass in the overburden and floor during longwall mining. A modified caving algorithm is incorporated into FLAC3D 9.0, augmented with the IMASS constitutive model, to accurately replicate the fracturing response of various strata. This study aimed to analyze the longwall caving performance, overburden fracturing response, and shield support characteristics to optimize the mining process and enhance safety. The numerical analysis revealed a progressive stress release at the longwall face, attributed to damage in the form of spalling, which was accompanied by a high level of displacement. The fracture process zone above the shield canopy was not significant, indicating the effective performance of the shield in controlling the roof. However, the floor heave highlights the need for the implementation of effective risk and safety measures. Goaf is predicted to form with a longwall advance rate of 25.0–30.0 m, resulting from progressive macroscopic fracturing caused by the development of cracks initiated by bedding plane and rock mass failures. Above the caved zone, an active fracture zone is observed to evolve due to the continuous longwall mining and caving process.